Insights on environmental effects - Seethaler, Sherry, 1970- (FT Press Delivers elements., 2011)
"This Element is an excerpt from Curious folks ask 2: 188 real answers on our fellow creatures, our planet, and beyond (ISBN: 9780137057399) by Sherry Seethaler"--Resource description page.